Anaplastic lymphoma kinase (ALK) gene rearrangements in radiation‐related human papillary thyroid carcinoma after the Chernobyl accident. (26th May 2018) - Arndt, Annette; Steinestel, Konrad; Rump, Alexis; Sroya, Manveer; Bogdanova, Tetiana; Kovgan, Leonila; Port, Matthias; Abend, Michael; Eder, Stefan
Abstract: Childhood radiation exposure has been associated with increased papillary thyroid carcinoma (PTC) risk. The role of anaplastic lymphoma kinase ( ALK ) gene rearrangements in radiation‐related PTC remains unclear, but STRN‐ALK fusions have recently been detected in PTCs from radiation exposed persons after Chernobyl using targeted next‐generation sequencing and RNA‐seq. We investigated ALK and RET gene rearrangements as well as known driver point mutations in PTC tumours from 77 radiation‐exposed patients (mean age at surgery 22.4 years) and PTC tumours from 19 non‐exposed individuals after the Chernobyl accident. ALK rearrangements were detected by fluorescence in situ hybridisation (FISH) and confirmed with immunohistochemistry (IHC); point mutations in the BRAF and RAS genes were detected by DNA pyrosequencing. Among the 77 tumours from exposed persons, we identified 7 ALK rearrangements and none in the unexposed group. When combining ALK and RET rearrangements, we found 24 in the exposed (31.2%) compared to two (10.5%) in the unexposed group. Odds ratios increased significantly in a dose‐dependent manner up to 6.2 (95%CI: 1.1, 34.7; p = 0.039) at Iodine‐131 thyroid doses >500 mGy. In total, 27 cases carried point mutations of BRAF or RAS genes, yet logistic regression analysis failed to identify significant dose association. To our knowledge we are the first to describe ALK rearrangements in post‐Chernobyl PTC samples using routine methods such as FISH and IHC. Our findings further support the hypothesis that gene rearrangements, but not oncogenic driver mutations, are associated with ionising radiation‐related tumour risk. IHC may represent an effective method for ALK‐screening in PTCs with known radiation aetiology, which is of clinical value since oncogenic ALK activation might represent a valuable target for small molecule inhibitors.